Pengembangan dan Pendampingan Web Profil Pondok Pesantren Ibnu Al-Mubarok Pekanbaru - Loneli Costaner; Guntoro Guntoro; Lisnawita Lisnawita (Universitas Lancang Kuning, 2022)
Pondok Pesantren Ibnu Al-Mubarok is an Islamic Education Institution located on Jl. Sri Palas, Rumbai Hill, Kec. Rumbai, Pekanbaru City, Riau. The Islamic boarding school has been running for about 3 years and there are more than 100 students participating in the activities of this Islamic boarding school. This Islamic boarding school is not only engaged in education, but also in agriculture, animal husbandry and the economy. The website is a digital page that can be used to share information, documents, and various other things through the internet. The partner problem at the Ibnu Al-Mubarok Islamic Boarding School is that there is no website that can be used as a medium for delivering information and promotions. Therefore, it is necessary to develop and assist the web profile of the Ibnu Al-Mubarok Islamic Boarding School. The methods for implementing this service are preparation and planning, field surveys and interviews, data collection, website design and development, implementation of mentoring and website handover, evaluation and final reporting. The results of the service activities are in the form of a web profile of the Ibnu Al-Mubarok Islamic Boarding School that can be accessed online.